2017
DOI: 10.1017/s0025315417000613
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and population structure ofOctopus mimusfished in a Marine Protected Area of Ecuador

Abstract: Octopus mimus is the main octopus targeted by the small-scale fishery in the Eastern Pacific. Commercial catches of octopus from the Reserva de Producción Faunística Marino-Costera Puntilla de Santa Elena (REMACOPSE) Marine Protected Area in Ecuador were sampled from July to December 2013 in order to describe the reproduction and population structure of this octopus. The 4171 sampled octopuses ranged from 56 to 250 mm in mantle length (ML) and 45 to 3178 g in body weight (BW). Mean octopus weight did not chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
1
0
2
Order By: Relevance
“…Moreover, he showed that the environmental conditions in Red Sea are more suitable for O. vulgarsis than in the Mediterranean Sea. (Markaida, et al 2018) used 4171 sampled Octopuses ranged from 56 to 250 mm in mantle length (ML) and 45 to 3178g in body weight in Ecuador waters postulated that sex ratios didn`t significantly shift from expected 1:1 in most samples, while in this study 50% only of morphometric data were significant according, T test. 402 samples of Octopus were investigated by Maulita et al (2018) in Indonesia, gave that a positive relationship between weight gain and Octopus length and increase in length faster than growth weight.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, he showed that the environmental conditions in Red Sea are more suitable for O. vulgarsis than in the Mediterranean Sea. (Markaida, et al 2018) used 4171 sampled Octopuses ranged from 56 to 250 mm in mantle length (ML) and 45 to 3178g in body weight in Ecuador waters postulated that sex ratios didn`t significantly shift from expected 1:1 in most samples, while in this study 50% only of morphometric data were significant according, T test. 402 samples of Octopus were investigated by Maulita et al (2018) in Indonesia, gave that a positive relationship between weight gain and Octopus length and increase in length faster than growth weight.…”
Section: Discussionmentioning
confidence: 58%
“…En el Pacífico mexicano el pulpo se extrae mediante buceo libre, scuba y trampas (López-Uriarte et al, 2005;Markaida et al, 2018;Sauer et al, 2019). No existe ningún plan de manejo pesquero y sólo hay una norma oficial que regula la captura de O. hubbsorum=O.…”
Section: Regulación Pesquera De Pulpo En El Pacífico Orientalunclassified
“…La pesquería de O. mimus está regulada únicamente en Perú y Chile por medio de una talla mínima de captura y las temporadas de veda regionales (Markaida y Gilly, 2016;Markaida et al, 2018;Sauer et al, 2019). En Ecuador, no se tienen registros de estadísticas pesqueras y no existe un plan de manejo para esta especie (Markaida y Gilly, 2016).…”
Section: Regulación Pesquera De Pulpo En El Pacífico Orientalunclassified